Matplotlib plotting cookbook : learn how to create professional scientific plots using matplotlib, with more than 60 recipes that cover common use cases - Devert, Alexandre (Quick answers to common problems., 2014)
This book follows a cookbook style approach that puts orthogonal and non-redundant recipes in your hands. Rather than rehashing the user manual, the explanations expose the underlying logic behind Matplotlib. If you are an engineer or scientist who wants to create great visualizations with Python, rather than yet another specialized language, this is the book for you. While there are several very competent plotting packages, Matplotlib is ""just"" a Python module. Thus, if you know some Python already, you will feel at home from the first steps on. In case you are an application writer, you wo